PENGARUH MEKANISME GOOD CORPORATE GOVERNCE TERHADAP KINERJA KEUANGAN - Rifka, Ode Karmila; Ratnasari, Fina (Publika Citra Media, 2025)
This research aims to determine the influence of Good Corporate governance mechanisms on financial performance, including institutional ownership, managerial ownership, board of commissioners, board of directors, audit committee on financial performance. This research was conducted at the Consumer Non-Cyclicals company. The type of research used is quantitative and the data used is secondary data in the form of annual financial reports published on the Indonesia Stock Exchange (BEI) in 2019–2023. Samples were collected using the purposive sampling method. The amount of data collected was 60 observation data. Data were processed using the Eviews 12 Statistical Program to test hypotheses using multiple linear regression analysis. The results of the F test show that institutional leadership, managerial ownership, board of commissioners, board of directors, audit committee, together have a simultaneous influence on financial performance. The t test results show that managerial ownership has a positive effect on financial performance, while institutional ownership, the board of commissioners, the board of directors and the audit committee have no effect on financial performance.